The association between decidual vasculopathy and abnormal uterine artery Doppler measurement. (9th June 2022) - Stevens, Droïma; Schiffer, Veronique; Severens‐Rijvers, Carmen; de Nobrega Teixeira, Johnny; van Haren, Ashlee; Spaanderman, Marc; Al‐Nasiry, Salwan
Abstract: Introduction: Placental syndrome is an umbrella term encompassing the clinical phenotypes of preeclampsia and fetal growth restriction, and is associated with high maternal and neonatal morbidity. In women with placental syndrome, histologicl examination of the uteroplacental unit commonly demonstrates pathological lesions, such as decidual vasculopathy. Decidual vasculopathy are pathological changes in the spiral arteries, which are associated with adverse outcome in preeclampsia and long‐term maternal cardiovascular health. The relation between placental syndrome phenotypes and placental pathology has been previously demonstrated; however, the role of uteroplacental Doppler measurements as a link between placental syndrome phenotypes and the underlying placental pathology is still unclear. We hypothesized that decidual vasculopathy is associated with abnormal uteroplacental Doppler profiles and ultrasound placental parameters, independent of clinical phenotype. Material and Methods: We performed a retrospective analysis of data from a prospective cohort of pregnancies with placental syndrome, as well as cases without hypertensive disease or fetal growth restriction. The study group was divided into women with decidual vasculopathy on histologic analysis of placental specimen and those without the lesions. Outcome parameters included maternal and fetal Dopplers, estimated fetal weight, placental weight and thickness, placental lacunae and abnormal placental calcification. Results: Compared with the women without the lesions ( n = 91), the group with decidual vasculopathy ( n = 25) had a higher mean uterine artery pulsatility index (1.70 vs 0.81, p < 0.001) and uterine artery pulsatility index percentile (>p99 vs p67, p < 0.001). Decidual vasculopathy was associated with abnormal uterine artery Doppler profile (defined as pulsatility index p > 95 and/or bilateral notch) (82%) compared with women without the lesions (33%) (odds ratio [OR] 9.3, 95% CI 2.4–36.0), which remained significant after adjusting for possible confounding factors preeclampsia, tobacco use and gestational age at birth (OR 7.1, 95% CI 1.3–39.1). Decidual vasculopathy was not associated with fetal Doppler abnormalities or placental parameters and only modestly so with lower cerebroplacental ratio ( p = 0.036). Conclusions: Histologic decidual vasculopathy is associated with abnormal uterine artery Doppler, independent of clinical phenotype during pregnancy.